Integrated Skill in English Language Learning: Examining Folklore-Implemented Teaching Toward EFL Students’ English Skill - Sulfany Tineh; Olga A. Rorintulus; Ceisy N. Wuntu (Universitas Muhammadiyah Enrekang, 2023)
This correlational study investigates the impact of folklore-implemented teaching on the integrated English language skills of English as a Foreign Language (EFL) students. Embracing a holistic approach to language learning, the study explores the interconnected development of listening, speaking, reading, and writing skills when exposed to the immersive context of folklore narratives. The study employs a correlational research design to analyze the associations between folklore-implemented teaching and the enhancement of various language skills. Utilizing qualitative and quantitative data collection methods, including questionnaire, observations, and literature study, the research seeks to discern patterns and correlations that elucidate the potential benefits of integrating folklore into the EFL curriculum. The findings contribute valuable insights into the effectiveness of folklore-based instruction in cultivating not only linguistic proficiency but also cultural awareness among EFL learners, where from data processing, sig 0.039 < 0.05 means reject Ho, thus it can be understood that there is a significant correlation or relationship between the folklore-implemented and student English skills in integrated learning. The results may inform instructional practices and curriculum design, providing a foundation for the integration of folklore as a pedagogical tool to enhance the integrated language skills of EFL students. Ultimately, the study contributes to the ongoing discourse on innovative and culturally relevant approaches to language education, aiming to advance the quality and efficacy of English language instruction for diverse learner populations.